CORRELATION OF SEVERE HEAD INJURY EPIDURAL HEMATOMA TREPANATION RESPOND TIME WITH OUTCOME - Santoso, Mochamad Istiadjid Eddy; Rahayu, Masruroh; Balafif, Fachriy (Malang Neurology Journal, 2016)
Background. Epidural hematoma is intracranial hemorrhage, due to skull fracture caused by head injury which there is a blood accumulation between the layers of duramater and the skull. Objective. To determine the corellation of epidural hematoma trepanation respond time with outcome. Methods. A retrospective observational analytic study (cross sectional) with 30 samples taken in Saiful Anwar Hospital Malang from June to August 2012. The independent variable in this study is trepanation respond time that divided into trepanation respond time less than 6 hours, between 6-12 hours, between 12-18 hours, between 18-24 hours, and more than 24 hours while the dependent variable in this study is the outcome of the patient. Secondary data were taken using medical records. The data were analyzed using independent T-test, spearman correlation test, kruskall walis test, and ROC test with confidence level 95% (Î±=0.005). Results. The analysis shows a significant corelation between severe head injury epidural hematoma trepanation respond time with the outcome.Conclusion. Faster trepanation respond time will have better outcome.